Answer: 3^5 / 3^(-2) = 3^(3)
Answer: 
Step-by-step explanation:
Remembert that, by definition:
→ 
Then, you can rewrite
in exponential form:

Now you can solve for the variable "x":
Add 6 to both sides of the equation:


And finally you must divide both sides of the equation by 2, then:

Answer:
Step-by-step explanation:
AB=
=
AC=
=
Answer:
duno
Step-by-step explanation:
duno duno
Answer: x - 2.6 = 72.8
x is the number which Dan was thinking (x > 2.6)
we have:
x - 2.6 = 72.8
Step-by-step explanation: